STUDI TENTANG SARANA PRASARANA PRAKTIK PADA MATA PELAJARAN MELAYANI MAKAN DAN MINUM DI BIDANG KEAHLIAN JASA BOGA DI SMK N 2 BUKITTINGGI - Yuliardi, Roni; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The background of this research is the findings about there are some students have bad achievement in food and drink serving, which are 45 students or 64.36%, it’s expected cause of the lack facilities in practice. The aim of this research is to describe the practice facilities for food and drink serving in SMKN 2 Bukittinggi, including : furniture, linen, and serving tools. And also the practice room. The kind of this research is descriptive research with qualitative approach. The object of this research is the practice facilities for food and drink serving. Data resource is X grade students and the teacher of food and drink sercing in SMK N 2 Bukittingi. Data collection did by using interview, observation and documentation. Data analyzed by using qualitative descriptive method.